A multiscale framework for evaluating three-dimensional cell mechanics in fibril-reinforced poroelastic tissues with anatomical cell distribution – Analysis of chondrocyte deformation behavior in mechanically loaded articular cartilage - Tanska P; Venäläinen MS; Erdemir A; Korhonen RK (ELSEVIER SCI LTD, 2022)
Characterization of the mechanical environment of cells in collagenous biological tissues during different daily activities is crucial for understanding the role of mechanics on cell biosynthesis and tissue health. However, current imaging methods are limited in characterizing very fast deformations of cells. This could be achieved with computational multiscale modeling, but current models accommodating collagen fibril networks and poroelastic ground matrix have included only a single cell. In this study, a workflow was developed for generating a three-dimensional multiscale model with imaging-based anatomical cell distributions and their micro-environment (pericellular and extracellular matrix). Fibril-reinforced poroelastic material models with (FRPES) and without (FRPE) swelling were implemented into the model and simulations were performed for evaluating cell deformations before and after experimental loading conducted for rabbit knee joint cartilage. We observed that the cells experienced considerably different deformation based on their location in all models. Both FRPE and FRPES models were able to predict the trends in the changes in cell deformations, although the average and median magnitudes differed between the model predictions and experiments. However, the FRPES model results were generally closer to the experimental results. Current findings suggest that morphological properties of cells are affected by the variations in the tissue properties between the samples and variations within the sample caused by the measurement geometry, local structure and composition. Thus, it would be important to consider the anatomical distribution and location of multiple cells along with the structure of fibril networks if cell deformation metrics are evaluated in collagenous tissues. (C) 2020 The Author(s). Published by Elsevier Ltd.